Expressions of power through the architectural sequence of the pre-hispanic monumental building of Campoy - Bazán Castillo, José (2021)
This article presents the results obtained from the study carried out with limited excavations of the pre-Hispanic building of Campoy, located on the right bank of the lower middle valley of Rímac, in the current one in the district of San Juan de Lurigancho. The interventions were part of the work objectives of the Huaca Fortaleza de Campoy Archaeological Research Project, whose research and protection interventions of the complex were promoted by the Institute of Culture, History and Environment ICHMA in 2017. The archaeological record has us allowed documenting various architectural designs, technological features and associated resources both inside and outside of the environments of a residence that would have been part of a monumental construction project, as evidenced by the superposition of structures that were consolidated as an expression of the symbolic power achieved by a certain group of individuals during the late periods of the Andean chronology.